2019
DOI: 10.1029/2018gl080363
|View full text |Cite
|
Sign up to set email alerts
|

The Asymmetry of Vertical Velocity in Current and Future Climate

Abstract: A fundamental aspect of vertical velocities in the atmosphere is their asymmetric nature, with stronger upward than downward motions. Here we study this asymmetry from a synoptic‐scale perspective, by employing a storm‐tracking algorithm in observations and climate change simulations. We show that midlatitude cyclones and anticyclones are both skewed toward stronger upward motions, and that this asymmetry intensifies in a warmer climate. Downward motions are generally influenced by changes in the dry static st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 29 publications
(50 reference statements)
3
18
0
Order By: Relevance
“…The anticyclonic orientation increases toward lower latitudes. This meridional dependence of the mean trough orientation is in agreement with the conventional interpretation of cyclonic and anticyclonic wave life cycles and the associated wave breaking, which occurs poleward (cyclonic) or equatorward (anticyclonic) of the mean jet position (Thorncroft et al, 1993). Over northern Africa, the climatological trough orientation is strongly anticyclonic.…”
Section: Extended Winter (November-march)supporting
confidence: 88%
See 3 more Smart Citations
“…The anticyclonic orientation increases toward lower latitudes. This meridional dependence of the mean trough orientation is in agreement with the conventional interpretation of cyclonic and anticyclonic wave life cycles and the associated wave breaking, which occurs poleward (cyclonic) or equatorward (anticyclonic) of the mean jet position (Thorncroft et al, 1993). Over northern Africa, the climatological trough orientation is strongly anticyclonic.…”
Section: Extended Winter (November-march)supporting
confidence: 88%
“…A trough or a ridge tilts cyclonically if it forms under cyclonic shear, while it acquires an anticyclonic orientation if it forms under anticyclonic shear (Davies et al, 1991;Thorncroft et al, 1993). In the case of a pronounced equatorward (poleward) excursion of a trough (ridge), it may wrap up and undergo irreversible deformation in a wave-breaking event (McIntyre and Palmer, 1983;Thorncroft et al, 1993). Under anticyclonic shear, the trough deforms into a narrow band, called a streamer, which crosses the jet and extends equatorward of the mean jet position and cut-off formation may occur.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, other work (using idealized baroclinic life cycle simulations) has shown that higher moisture content will lead to an increased asymmetry between strong, narrow ascent, and broad, slow descent in the midlatitudes [45]. This signal has also been found in GCMs [46]. Corresponding structural changes to the precipitation distribution have also been identified using cyclone-centric compositing techniques, with the heaviest precipitation concentrated near the center of the ETCs in a warmer climate [41,47].…”
Section: Changes In Extratropical Cyclones From Idealized Modelsmentioning
confidence: 69%